Green synthesis of high throughput hydrogen peroxide via sub-atmospheric plasma-water interaction - Rathore, Vikas (Environmental technology, 2025)
Plasma-activated water (PAW), enriched with reactive species such as hydrogen peroxide (H2O2), presents a sustainable and versatile solution for wastewater treatment, disinfection, agriculture, and biomedical applications. This study investigates the effects of key plasma parameters - treatment time, input power, water purity, and chamber pressure - on H2O2 production. A statistical framework combining response surface methodology (RSM), regression analysis, ANOVA, effect estimation, and marginal means was employed to model and analyze these influences. Among the variables, treatment time had the most significant impact, followed by water purity and input power. Deionised water produced higher H2O2 concentrations due to reduced ion buffering capacity. Under optimised conditions (3 min, 300 W, 100 mmHg), a maximum H2O2 concentration of 35 mg·L⁻¹ was achieved, with an energy efficiency of 42.9 g kWh-1. Additionally, the energy efficiencies for NO3-, NO2-, and dissolved O3 were 73.5, 14.7, and 6 g kWh-1, respectively. These findings provide valuable insights for tailoring PAW production toward specific oxidative applications